MODERN CRIMINOLOGICAL CHARACTERISTICS OF CRIME IN RURAL REGIONS (continuation) - G. V. Antonov-Romanovskiy; G. F. Koimshidi; D. K. Chirkov; A. A. Litvinov; A. N. Trushenko (Russian Journal of Economics and Law)
Objective: to study the relevance of the problem and characteristics of crime in rural regions of the Russian Federation, which is determined, on the one hand, by the complexity of the criminal situation in rural regions, the acuteness of the problems of crime prevention organization; and on the other hand by the lack of research of criminological problems of rural crime. Methods: ascent from the abstract to the concrete; system-structural and comparative analysis; historical; dynamical and statistical methods, as well as the concrete sociological methodology of rural crime evaluation. Results: specific features of crime in rural regions and its social danger are shown in comparison with urban crime. The effective directions are proposed for improving counteraction against the crimes in view. Scientific novelty: the article considers the trends of crime in rural regions, a comparative analysis is carried out of the registered crimes dynamics in rural and urban regions. As a result, the following peculiarities were revealed: in rural regions the crime rate is higher than in the cities, in addition, in rural regions there is a serious status and scope (in comparison with cities) of destruction of villagers’ murdering and causing grievous bodily harm as a result of criminal encroachments; the level of the killed village citizens in Russia in the last three years was stable and is more than twice higher than the level that characterizes urban crime, and is almost one and a half times higher than the number of persons in the cities suffering from grievous bodily harm, etc. The authors indicate the complexity of the criminal situation in the village. The tendency of reducing the number of crimes registered in rural areas in 2009-2012, does not reflect its real condition, because during the last years this trend is due to artificial regulation of the amount of crimes reflected in the statistical reports. Practical value: the results show the degree of public danger of rural crime, and can serve as the basis to develop effective solutions for its prevention.